Combination Therapy: Murottal and Slow Stroke Back Massage (SSBM) Affecting the Blood Pressure of Hemodialysis Patients - Melastuti, Erna; Nursalam, Nursalam; Sukartini, Tintin; Janitra, Fitria Endah (International Journal of Psychosocial Rehabilitation, 2020)
For the clinical condition of hemodialysis, patients can be seen to struggle with many parameters such as interdialytic weight gain, blood pressure before and after hemodialysis, blood sodium levels, and the patient’s physical activity. Measurement of blood pressure is the simplest way to assess these factors because blood pressure can describe the hemodynamic situation of the patient at that time. With optimal blood pressure, it is expected that the patient’s quality of life will be good. To achieve optimal blood pressure, complementary therapies can be performed, one of which is a combination therapy of murottal and Slow Stroke Back Massage (SSBM). The purpose of this study was to determine the effect of murottal and SSBM on changes in blood pressure in hemodialysis patients. This study had a quasi-experiment one group pretest and posttest design, involving 17 respondents chosen by a purposive sampling technique. Respondents in this study were hemodialysis patients who had hypertension and fulfilled the inclusion and exclusion criteria. Measurement of blood pressure was done with a sphygmomanometer before and after combination therapy with murottal and SSBM. The data normality test was done using the Shapiro-Wilk test and data analysis was done using a paired t-test. The mean blood pressure before giving the combination therapy, systolic pressure was 170.41 mmHg and diastolic was 119.18 mmHg. The mean blood pressure after combination therapy was 145.94 mmHg for systolic pressure and 108.65 mmHg for diastolic. There were significant changes in systolic and diastolic blood pressure after murottal and SSBM combination therapy (p <0.000). There were significant changes in systolic and diastolic blood pressure after giving combination therapy with murottal and SSBM. Murottal Al-Qur’an can reduce cortisol levels which are stress hormones that contribute greatly to high blood pressure. SSBM can increase the serotonin hormone in the body, reduce stress and release norepinephrine and epinephrine hormones which play a role in lowering blood pressure.